Novel in-situ lamella fabrication technique for in-situ TEM - Nicolosi, Valeria; Canavan, Megan; Daly, Dermot; Rummel, Andreas; McCarthy, Eoin K.; McAuley, Cathal (My University, 2018)
In-situ transmission electron microscopy is rapidly emerging as the premier technique for characterising materials in a dynamic state on the atomic scale. The most important aspect of in-situ studies is specimen preparation. Specimens must be electron transparent and representative of the material in its operational state, amongst others. Here, a novel fabrication technique for the facile preparation of lamellae for in-situ transmission electron microscopy experimentation using focused ion beam milling is developed. This method involves the use of rotating microgrippers during the lift-out procedure, as opposed to the traditional micromanipulator needle and platinum weld. Using rotating grippers, and a unique adhesive substance, lamellae are mounted onto a MEMS device for in-situ TEM annealing experiments. We demonstrate how this technique can be used to avoid platinum deposition as well as minimising damage to the MEMS device during the thinning process. Our technique is both a cost effective and readily implementable alternative to the current generation of preparation methods for in-situ liquid, electrical, mechanical and thermal experimentation within the TEM as well as traditional cross-sectional lamella preparation.
Keywords: In-situ transmission electron microscopy; specimen preparation; Focused ion beam; Lamella preparation; In-situ heating; Lift-out; Low-kV milling